Combustible solid waste thermochemical conversion : a study of interactions and influence factors - Zhou, Hui (Springer, 2017)
This book is written by Dr. Hui Zhou as a Ph. D. dissertation in Tsinghua University, China. It establishesthe thermochemical characteristics of model compounds in combustible solid waste (CSW), and delineates the influence of different factors on the thermochemical characteristics and the influence interactions between model components have on the thermochemical characteristics. The works provide a theoretical basis for the clean and high-efficiency utilization of CSW as well as the basic knowledge for further understanding the thermochemical conversion mechanisms of complex fuels. Researchers and engineers in the field of thermal engineering and environmental engineering can benefit from the book.
"Doctoral thesis accepted by Tsinghua University, Beijing, China."
Keywords: Refuse as fuel.; Incineration.; Thermochemistry.; Pyrolysis.; elektronické knihy; electronic books